2009
DOI: 10.2176/nmc.49.413
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Subacute In-stent Restenosis After Carotid Artery Stenting due to Plaque Protrusion -Case Report-

Abstract: A 70-year-old male presented with transient ischemic attacks manifesting as right hemiparesis and motor aphasia due to severe left cervical internal carotid artery stenosis. Carotid artery stenting (CAS) using a flow-reversal system was performed without complications. However, the patient exhibited transient right hemiparesis and motor aphasia 10 days after CAS. Emergent angiography demonstrated in-stent restenosis. In-stent percutaneous transluminal angioplasty and CAS were performed successfully using a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…Despite neurological-protections during the procedure, there have been several reports about delayed plaque protrusion after CAS, especially in the patients with carotid vulnerable plaque 14,20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite neurological-protections during the procedure, there have been several reports about delayed plaque protrusion after CAS, especially in the patients with carotid vulnerable plaque 14,20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are many case reports of the appearance of serious ischemic symptoms in the subacute phase after CAS or additional revascularization needed due to repeated ischemic attacks. [9][10][11][12][13][16][17][18][19][20] LDAs on CTA in the subacute phase may be associated with these ischemic complications. Appropriate treatment based on early detection of LDA on CTA might decrease the incidence of perioperative complications, consequently improving the results of CAS.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] In a review of stent-related thrombosis after CAS, Moulakakis et al emphasized that antiplatelet drugs were important for its prevention. They reported that etiological factors for thrombus formation included insufficient administration of antiplatelet drugs, drug resistance, inherent or acquired thrombotic disorders including cancer, and discontinuation of antiplatelet drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, delayed cerebral infarction, occurring within a few days after the procedure, is still observed with a fixed probability, remaining one of the current problems with CAS to be addressed. 6,7) Although plaque protrusion is suggested to be a primary cause of delayed cerebral infarction, there remains no established preventive measure and at present, early detection is considered important. 6-9) Shinozaki et al 2) compared plaque protrusion rates of detection between angiography and IVUS immediately after CAS in 77 consecutive patients, reporting that the detection rate was 2.6% by angiography alone, but 7.8% by IVUS, suggesting usefulness of IVUS.…”
Section: Disclosure Statementmentioning
confidence: 99%